Chronic Cough: Etiology, Management and Challenges - B Shingore, Dr. Pradeep (International Journal of Innovative Research in Medical Science, 2018)
Cough is one of the commonest symptoms of lung disease and is a frequent problem encountered in general practice as well as in hospital patients. It is a common symptom of most respiratory disorders and is a most common reason for patients of all ages to consult their doctor Chronic cough in general adult populations global prevalence of 9.6% was found compared to India that was less than 5%.[1] Chronic cough poses a great diagnostic and management challenge due to various etiologies and is commonly considered to be caused by gastroesophageal reflux, post-nasal drip or asthma. This article covers the etiology and mechanism of cough with recent advances in the field of cough and showing some of the diagnostic and management challenges.